Stability Improvement and Solid-State of Sauropus androgynus Leaf Extract Solid Dispersion Using a Carrier of Polyvinylpyrrolidone - Jingga, Mutiara Dara; Barikah, Kuni Zuaimah; Wicaksono, Yudi (Indonesian Journal of Applied Research (IJAR), 2025)
The Sauropus androgynus leaf contains various phytochemical compounds with various pharmacological activities. However, phytochemical compounds in plant extracts are generally unstable during storage or formulation. This study aimed to prepare S. androgynus leaf extract solid dispersions and evaluate the solid-state properties and stability. Solid dispersions were produced through solvent evaporation using polyvinylpyrrolidone (PVP) as the carrier. Solid dispersions were characterized by powder X-ray diffractometer (PXRD), differential scanning calorimeter (DSC), and scanning electron microscope (SEM). Solid dispersions were stored at a temperature of 60 °C for 30 days, and the stability was determined by measuring the total flavonoid content. The preparation results showed that solid dispersions of S. androgynus leaf extract with PVP K30 and PVP K90 carriers were amorphous solids with a glass transition temperature of 160-170 °C. The phytochemical content of the extract in solid dispersion showed degradation at a temperature of 175.3 - 188.3 °C. At a temperature of 60 °C for 30 days, the decrease of total flavonoid content in solid dispersion was lower than in pure extract. Thus, the formation of solid dispersion of S. androgynus leaf extract with PVP K30 and PVP K90 carriers can increase the stability of phytochemical compounds in S. androgynus leaf extract.